2022
DOI: 10.30919/es8e779
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Green Composites and Their Applications

Abstract: Conventional petroleum-based toxic and non-biodegradable composites in comparison with natural fiber composites and hybrid natural fiber composites find attraction in the automobile industry, manufacturing, aerospace, sporting goods, construction, and marine applications due to the lower ecological risks. Green composites have the challenge of replacing conventional materials like steel, wood, and non-biodegrading polymers. Specific material features of green composites for particular loading and load-bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…T i is the mean value of the different factors at different levels and t i value is one fifth of T i . The range value (R‐value) is the difference value between the maximum and minimum values of t i (t i,max –t i,min ) [13] . The R values in Table 2 show that the KH560 content has the greatest influence on the modification effect (settling height), followed by the volume ratio of ethanol/water, and finally, the pH.…”
Section: Resultsmentioning
confidence: 99%
“…T i is the mean value of the different factors at different levels and t i value is one fifth of T i . The range value (R‐value) is the difference value between the maximum and minimum values of t i (t i,max –t i,min ) [13] . The R values in Table 2 show that the KH560 content has the greatest influence on the modification effect (settling height), followed by the volume ratio of ethanol/water, and finally, the pH.…”
Section: Resultsmentioning
confidence: 99%
“…These materials are increasingly employed in therapeutic devices, including temporary implants and three-dimensional scaffolds for tissue engineering. [8][9][10][11] Biopolymers, derived from living organisms, encompass a wide range of sources, such as plants like corn and soybeans, certain trees, and even certain bacteria. [12][13][14][15] Numerous studies have demonstrated the potential of biopolymers in bone tissue engineering, primarily attributed to their biocompatibility, biodegradability, and ability to mimic the extracellular matrix of natural bone.…”
Section: Biopolymers For Bone Tissue Engineeringmentioning
confidence: 99%
“…These models apply to variable ranges, such as quartz powder substitution (0-20% by cement weight), quartz sand substitution (0-50% by crushed limestone weight), and water curing temperatures (from 25 • C to 95 • C) [15][16][17]. In this study, an attempt has been made to find out the compressive strength of the cube with different proportions of copper slag and quartz with a cement-concrete mix design [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%